Thank you for tomorrow : HISK laureates 2010 in conversation with Jan Debbaut - Debbaut, Jan; HISK, Gent (Gent : HISK, 2010)
Baelen, Steven ; Catalao, André ; Cottin, Audrey ; Dhondt, Lara ; Echigo, Masashi ; Gruber, Assaf ; Mikulicova, Jitka ; Mücke, Carola ; Otten, Femmy ; Van de Velde, Rinus ; Von Gogh, Lauren ; Waeghe, Colin
Published in conjunction with the exhibition 'Thank you for tomorrow' at De Zwarte Zaal at Gent, 18.12.2010-24.12.2010 ; 11.01.2011-18.01.2011
boek